Preparation and Properties of Ni–W Composite Coatings Reinforced by Graphene Nanoplatelets. Issue 8 (5th May 2021) - Cheng, Desen; Zhang, Lan; Zhan, Zhuoyi; Xia, Huimin; Ma, Kaiqiang; Ma, Huizhong; Gao, Yuan
Abstract : Metal enhancement is crucial for reducing energy use and material waste. Composite electrodeposition is an economic and efficient method for improving the surface properties of metals. Herein, Ni–W matrix composite coatings reinforced with graphene nanoplatelets (GNPs) are prepared on 7075 aluminum (Al) alloy plates by the co‐deposition technique. Characterization results reveal that the mechanical properties and corrosion resistance of the coating can be improved by the successful embedding of GNPs. The Ni–W/GNP coating exhibits rougher, cauliflower‐like morphology, higher microhardness (782.6 HV), lower wear rate (2.72 × 10 −5 mm 3 N −1 m −1 ), and better corrosion current density (18.19 μA cm −2 ) compared with the Ni–W coating (578.2 HV, 7.43 × 10 −5 mm 3 N −1 m −1, and 25.16 μA cm −2, respectively). Moreover, X‐ray diffraction (XRD) spectroscopy and analysis verify that the grain size is decreased for GNP‐reinforced composite coatings with a typical Ni‐based solid‐solution phase. Abstract : To further improve the properties of nickel‐tungsten (Ni‐W) coating, a Ni‐W‐graphene composite coating is successfully prepared on 7075 aluminum alloy substrates by the composite electrodeposition (co‐deposition) technology. The composite coating comprising graphene nanoplatelets wrapped in a Ni–W matrix exhibits a cauliflower‐like morphology with a higher microhardness, lower wear rate, and better corrosion resistance.